1996
DOI: 10.1093/mutage/11.6.573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxicity of stevioside and steviol using six in vitro and one in vivo mutagenicity assays

Abstract: Stevioside, a constituent of Stevia rebaudiana, is commonly used as a non-caloric sugar substitute in Japan. The genetic toxicities of stevioside and its aglycone, steviol, were examined with seven mutagenicity tests using bacteria (reverse mutation assay, forward mutation assay, umu test and rec assay), cultured mammalian cells (chromosomal aberration test and gene mutation assay) and mice (micronucleus test). Stevioside was not mutagenic in any of the assays examined. The aglycone, steviol, however, produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 26 publications
2
61
1
5
Order By: Relevance
“…Because steviol is known to be unstable in acid and gives rise to isosteviol, 21) the steviol seemed the most likely candidate for the genuine aglycon. This was substantiated by the evidence that signals due to the aglycon moiety in 13 C NMR spectra of the predominant fractions were found at almost the same position as those of authentic steviol glycosides. 22 24) The chemical shifts of several compounds are summarized in Table 2.…”
Section: Separation Of Stevia Sweetener Fraction From S Rebaudiana Mmentioning
confidence: 75%
See 3 more Smart Citations
“…Because steviol is known to be unstable in acid and gives rise to isosteviol, 21) the steviol seemed the most likely candidate for the genuine aglycon. This was substantiated by the evidence that signals due to the aglycon moiety in 13 C NMR spectra of the predominant fractions were found at almost the same position as those of authentic steviol glycosides. 22 24) The chemical shifts of several compounds are summarized in Table 2.…”
Section: Separation Of Stevia Sweetener Fraction From S Rebaudiana Mmentioning
confidence: 75%
“…The hot water extracts were resolved into 20 fractions by HPLC on an Amide 80 column. Each fraction was subjected to structural analysis by sugar composition analysis, ESI MS, ESI MS MS, 1 H NMR, 13 C NMR and or chemical analyses such as methylation analysis and mild alkaline or acid hydrolysis, and the structures of 21 steviol glycosides were established. The structures and relative amounts of the 21 steviol glycosides, on the basis of their UV absorbance at 210 nm and relative abundance of the fragment ions in ESI MS MS spectra, are compiled in Table 4 together with the composition of the stevia sweeteners of S. rebaudiana Bertoni.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some work has failed to demonstrate carcinogenic, teratogenic, mutagenic or toxic actions of stevioside (78), after oral administration to rats [108][109][110][111], at doses up to 1.2 % of the diet, and considering, therefore, a maximum ingestion recommendable of 7.94 mg·kg -1 ·d -1 for the human organism [112], others have demonstrated that steviol (24), an aglycone obtained from complete hydrolysis of stevioside, showed a high toxicity in pregnant females and embryos of hamsters, at doses of 0.75 and 1.00 mg·kg -1 ·d -1 , administered from 6 th to 10 th day of gestation [112][113][114]. The animals treated with these doses showed acute renal failure, embryotoxic effects such as weight loss and retardation of the process of fetal ossification, and death.…”
Section: R' = R" = Hmentioning
confidence: 99%